Eric Broekaert (1951-2016): the life and legacy of a TC pioneer and integrative thinker. Issue 3 (11th September 2017) - Vanderplasschen, Wouter; Vandevelde, Stijn; D'Oosterlinck, Franky; Vandevelde, Dirk; Naert, Jan; Yates, Rowdy
Abstract : Purpose: Eric Broekaert passed away shortly after the XVIth European Working group on Drug-Oriented Research (EWODOR)-conference in Rome on 28 September 2016. He was one of the great TC pioneers in Europe, who founded the first TC for addictions in Belgium (De Kiem) and co-founded the European Federation of Therapeutic Communities and EWODOR. He was a respected Professor of "Orthopedagogics" at Ghent University and a Member of the Editorial Collective of Therapeutic Communities: the International Journal of Therapeutic Communities . The paper aims to discuss the overview of the career of Eric Broekaert. Design/methodology/approach: In this obituary, the authors provide an overview of his career, major achievements and theoretical, methodological and integrative ideas, clustered around four typologies: university professor and scholar; manager and source of inspiration; TC pioneer and believer, and integrative thinker. Findings: Besides his obvious merits as a TC researcher and advocate, one of his major theoretical contributions has been the introduction of the holistic, integrative approach and the idea that diverse types of interventions, as well as methodological approaches can alternatively go together. Originality/value: He regarded TCs as the ultimate integration of various educational and therapeutic approaches to promote growth and quality of life among severely disadvantaged populations, such as drug addicts and children and adults with emotional and behavioural disorders.